GROUNDWATER QUALITY OF ANDHAKARANAZHY COAST, ALAPPUZHA, KERALA, INDIA - V. SIVANANDAN ACHARI; P. DEEPA b AND M.S. AMBILI (Indian J.Sci.Res., 2018)
Andhakaranazhy is a coastal village in Alappuzha district, Kerala, India, identified as one of the 26 th December 2004 tsunami affected coastal sections of Kerala. This area is particularly under severe water stress because of having only few dependable fresh water sources. To study the groundwater chemistry and fate of ions, eleven ground water sources (9 dug wells and 2 bore wells) have been monitored and water quality parameters analyzed for a period of time 2012-2016. The results were revealed that total iron exceeds the permissible limits of BIS standards in some of the groundwater sources (2012-2016). Based on the piper plots, the hydro chemical facies of the water is characterized by Ca 2+ - Mg 2+ -HCO 3- prominent over the years (2012-2016). Groundwaters mostly are suitable for irrigation purposes based on parameters evaluated. Corrosion indices reveals, the groundwater having scale forming behavior. Gibbs diagrams indicate the groundwater chemical composition of this region is controlled by weathering of rocks and evaporation. This study focuses the overall hydrogeochemistry of groundwater being tested for parameters measured and reported as sodium percent (Na %), sodium adsorption ratio (SAR), Kelly’s ratio (KR), permeability index (PI), magnesium adsorption ratio (MAR), Gibb’s plots, Langelier saturation index (LSI) and other similar values.